Health on equal terms? - Västra Götaland, 2015 - Health on equal terms, Västra Götaland - 2015 - Public Health Agency of Sweden (Region Västra Götaland, 2015)
The survey “Health on equal terms?” is a national survey, conducted every year since 2004. The Public Health Agency is responsible for the survey and Statistics Sweden (SCB) is responsible for the distribution, collection and registration. During the data collection in 2015, Region Västra Götaland ordered an additional sample for Västra Götaland County.

The additional sample in 2015 included all individuals aged 16-84 years living in Västra Götaland County, a total of 91,347 individuals. Including the national sample of Västra Götaland County the total number were 94,644 individuals. A part of the additional selection consisted a cohort of people from the survey in 2011.

A total of 52,348 individuals answered the questionnaire, representing a response rate of 55,5 percent.

The questionnaire was printed in two versions. The Public Health Agency designed the questions in the national questionnaire form. Region Västra Götaland excluded some of the questions in the national form and instead added three questions about work environment and the EQ5D-instrument. Both questionnaires covered issues of health, lifestyle, economic conditions, work and employment, and security and social relations. In addition to data collected through the questionnaires, registry data were also included.

Purpose:

The aim of the national survey was to investigate the health in the population and to show changes in the population's health over time as a follow up of the national health politics. The aim of the additional sample in Västra Götaland County was to investigate the health in the population in Västra Götaland County.

Undersökningen ”Hälsa på lika villkor?” är en stor nationell undersökning som genomförts varje år sedan 2004. Folkhälsomyndigheten ansvarar för undersökningen medan Statistiska centralbyrån (SCB) ansvarar för utskick, insamling och registrering av svar. I samband med undersökningen 2015 beställde Västra Götalandsregionen ett tilläggsurval för Västra Götalands län.

Tilläggsurvalet för 2015 års undersökning inkluderade samtliga invånare 16-84 år i Västra Götalands län och bestod av totalt 91 347 personer. Det totala antalet urvalspersoner, dvs. tilläggsurvalet samt urvalspersoner från Västra Götaland i det nationella urvalet var 94 644 personer. En del av tilläggsurvalet utgjordes av en kohort med personer som svarade på 2011 års undersökning.

Det var totalt 52 348 personer som besvarade frågeblanketten, vilket var 55,5 procent av urvalet.

Folkhälsomyndigheten utformade frågorna i den nationella frågeblanketten. Västra Götalandsregionen valde att exkludera några av frågorna i den nationella blanketten. Istället valde man att ta med tre egna frågor om arbetsmiljö och den så kallade EQ5D-frågan. Den nationella blanketten bestod av 73 numrerade frågor. Flera av dem hade delfrågor, vilket genererade totalt 102 frågor. Västra Götalands frågeblankett bestod av 69 numrerade frågor eller totalt 102 frågor inklusive delfrågor. Frågorna handlade bland annat om hälsa, levnadsvanor, ekonomiska förhållanden, arbete och sysselsättning samt trygghet och sociala relationer. Förutom de variabler som samlades in via frågeblanketten hämtades ett antal variabler från register.

Syfte:

Syftet med den nationella undersökningen var att ta reda på hur Sveriges befolkning mår och lever och även att följa upp den nya folkhälsopolitiken. Syftet med urvalet för Västra Götalands län var att ta reda på hur befolkningen i Västra Götalands län mår och lever.

Av tilläggsurvalet, exklusive kohorten från 2011, var det totalt 38 896 personer som svarade på blanketten, vilket motsvarade 51,7 %.
Hälsa på lika villkor? - Västra Götaland, 2015 - Hälsa på lika villkor, Västra Götaland - 2015
Keywords: Health Services; Hälso- och sjukvård; Physical Examination; Hälsokontroll; Dental Care; Tandvård; Hearing; Hörsel; Life Style; Livsstil; Medicine; Medicin; Exercise; Träning; Population Surveillance; Populationsövervakning; Hearing Loss; Hörselnedsättning; Socioeconomic Factors; Socioekonomiska faktorer; Tinnitus; Öronsusning; Urinary Incontinence; Urininkontinens; Anxiety; Ångest; Overweight; Övervikt; Diet; Kost; Alcohol Drinking; Alkoholkonsumtion; Work; Arbete; Asthma; Astma; Diabetes Mellitus; Diabetes; Eczema; Eksem; Public Health; Folkhälsa; Leisure Activities; Fritidsaktiviteter; Cardiovascular Diseases; Kardiovaskulära sjukdomar; Headache; Huvudvärk; Health; Hälsa; Health Status; Hälsotillstånd; Hypertension; Högt blodtryck; Body Weight; Kroppsvikt; Drug Utilization; Läkemedelsförsörjning; Gastrointestinal Diseases; Mag-tarmsjukdomar; Migraine Disorders; Migränsjukdomar; Oral Health; Munhälsa; Depression; Depression; Interpersonal Relations; Mellanmänskliga relationer; Mental Health; Psykisk hälsa; Registries; Register; Smoking; Rökning; Disease; Sjukdom; Pain; Smärta; Tobacco, Smokeless; Rökfri tobak; Social Support; Socialt stöd; Stress, Psychological; Psykologisk stress; Vision, Ocular; Syn; Sleep; Sömn; Sleep Wake Disorders; Sömn- och vakenhetsstörningar; Fatigue; Trötthet; Occupations; Yrken; Hypersensitivity; Överkänslighet; Feeding Behavior; Ätbeteende; HEALTH; HÄLSA